Water regimentation in the Pontine Plain between Astura and Fogliano in the dynamics of ancient population - Laura Ebanista (Groma)
The stretch of coast between Astura and Fogliano is characterized by a particular geomorphological situation linked to several difficulties in the drainage of the waters that have always generated marshes. In this contribution will be analysed the settlement and development dynamics of this particular territory from an archaeological point of view basing on the bibliographic and archive data, the survey and the photointerpretation. Considering the significant modifications that the territory has undergone because of the numerous reclamations, a reconstructions of the ancient ideography is also here proposed.